Tumor Mülleriano misto maligno uterino: estudo de parâmetros clínicos e morfológicos em uma série de casos - Mendonça, Lidia Almeida (2018)
Malignant Mixed Müllerian Tumor is a rare neoplasia of the female genital tract characterized by high aggressiveness. There are few descriptive studies about these tumors in our region. The aim of this study was to describe the clinical and anatomopathological features in a series of six cases. The average age of the patients was 70 years and the main clinical presentation was postmenopausal uterine bleeding. Preooperative misdiagnosis is a frequent ocurrence due to inadequate tumoral sampling in endometrial biopsies. The disease is often diagnosed in advanced stages. Despite early stage be considered a prognostic factor, even these tumors present high rate of progression or recurrence. The role of adjuvant therapy is not yet established.